Kilas Balik Peran Dakwah Anggota Legislatif Perempuan di DKI Jakarta - Kadriyah, S Maryamah (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This research stems from the importance of Muslim women's roles in politics as part of contemporary da'wah. The problem addressed is how Muslim female members of the DKI Jakarta Regional Legislative Council integrate Islamic values into public policy. This study aims to analyze their da'wah roles through structural approaches, such as strengthening religious institutions, empowering the economy, advocating for sharia-based policies, and enhancing family development. Using a descriptive qualitative method based on interviews and document analysis, the findings reveal that council members integrate da'wah with legislative tasks, resulting in positive impacts on policies promoting women's empowerment and strengthening family values based on Islamic principles..